Case Report: Intrahepatic Cholestasis of Pregnancy - D'silva, Precilla; Lobo, Jasmine Maria; Babu, Akhila Mol (Journal of Health and Allied Sciences NU, 2016)
Intrahepatic cholestasis of pregnancy (ICP) is a cholestatic disorder characterized by pruritus, elevated serum aminotransferases and bile acid levels with gradual onset in the second or third trimester of pregnancy, and spontaneous relief of signs and symptoms within two to three weeks after delivery.
Keywords: Intrahepatic Cholestasis(ICP); Pruritis; Bile Acid